Validity of Photosynthesis Topic Student Worksheet Based on Know Want Learned (KWL) Strategy to Facilitate Students’ Metacognitive Skill of 12Th Grade Senior High School - Agustin, Rosyida; Rahayu, Yuni Sri (Program Studi Pendidikan Biologi, FMIPA, Universitas Negeri Surabaya, 2021)
Metacognitive skill is one of the skills needed in community 4.0. This development research was aimed to produce valid student worksheet based on Know Want Learned (KWL) strategy for photosynthesis topic to facilitate students’ metacognitive skill. The student worksheet consists of three main phases of learning activities, namely Know, Want, and Learned phase which help to facilitate students' metacognitive skill. This development research used ADDIE development model. The research stage was begun by students, school curriculum, concept, and task analysis than continued with design and development of student worksheet stage in Biology Department, Mathematics and Natural Sciences Faculty, Universitas Negeri Surabaya. The student worksheet was then implemented to fifteen 12th grade students of MAN 5 Jombang. The data of student worksheet validity obtained from the validation of an education expert, a plant physiology expert, and a biology teacher that were analyzed based on mode. The validation result showed that the student worksheet was very valid with mode of 4,00. Based on these results, it can be concluded that the student worksheet was worthy to be used in facilitating student metacognitive skill. Keywords: Validity of student worksheet based on Know Want Learned (KWL), metacognitive skill, photosynthesis.